Electroplated synthesis of semi-rigid MoS2–rGO–Cu as efficient self-supporting electrode for hydrogen evolution reaction. (20th September 2020) - Huang, Junying; Chen, Mengting; Tang, Tao; Liu, Weipeng; Liu, Yingju
Highlights: A semi-rigid and self-supporting electrode was prepared by an easy electroplating. The semi-rigid electrode can be adjusted with different shapes. The catalytic properties for HER can be remained even shaped as an "S". The preparation steps were friendly and it can be easily fabricated in a factory. The detailed mechanism for such self-supporting electrode was investigated. Abstract: The self-supporting catalytic electrode is useful in the industry, since it can reduce the complex pre-treatment of catalytic materials and avoid the use of binders. In this work, a ternary self-supporting electrode including Cu mesh-supported graphene and molybdenum disulfide (MoS2 ) was prepared by electroplating zinc and hydrothermal reaction. Due to the excellent conductivity of copper and the hydrogen evolution catalytic ability of MoS2, this self-supporting electrode showed a low Tafel slope as 54 mV dec −1 and a current density of 400 mA cm −2 at an overpotential of -300 mV in hydrogen evolution reaction (HER). In addition, due to the metal flexibility of the Cu mesh substrate, the MoS2 –rGOCu ternary self-supporting electrode can be bent or cut into any desired shape. Even shaped as an elongated one, curved "S", this self-supporting electrode still kept itself from any deformation when hydrogen bubbles were rapidly generated. Therefore, a strategy for green, simple, and low-cost self-supporting electrode was provided, which may increase the large-scale operation of the catalytic electrode in HER. Graphical abstract: Image, graphical abstract